2022
DOI: 10.1093/cid/ciac571
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Immunocompromised Patients With Coronavirus Disease 2019 Caused by the Omicron Variant: A Prospective, Observational Study

Abstract: Background In the general population, illness after infection with the SARS-CoV-2 Omicron variant is less severe compared with previous variants. Data on the disease burden of Omicron in immunocompromised patients are lacking. We investigated the clinical characteristics and outcome of a cohort of immunocompromised patients with COVID-19 caused by Omicron. Methods Solid organ transplant recipients, patients on anti-CD20 thera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 23 publications
1
73
0
2
Order By: Relevance
“…We described 20% mortality in a single-center cohort of hospitalized transplant patients in Saudi Arabia infected with Omicron variants while a recent study in USA showed that the mortality of hospitalized transplant recipients during the Omicron surge was only 4%. The main reason for the high mortality in our study is the lower three doses vaccination status compared to the other study; 36% versus 89% [6]. In addition, COVID-19 monoclonal antibodies were used in 74% of patients in the second study while none of our patients received sotrovimab.…”
Section: Discussionmentioning
confidence: 66%
“…We described 20% mortality in a single-center cohort of hospitalized transplant patients in Saudi Arabia infected with Omicron variants while a recent study in USA showed that the mortality of hospitalized transplant recipients during the Omicron surge was only 4%. The main reason for the high mortality in our study is the lower three doses vaccination status compared to the other study; 36% versus 89% [6]. In addition, COVID-19 monoclonal antibodies were used in 74% of patients in the second study while none of our patients received sotrovimab.…”
Section: Discussionmentioning
confidence: 66%
“…With an overall 20% mortality rate, solid organ transplant recipients have worse outcomes after SARS-CoV-2 infection [ 1 ]. Even when infected by the less lethal SARS-CoV-2 Omicron variant, hospital admission rate is higher and the duration of symptoms is more prolonged in HTx patients, compared to non-immunocompromised individuals [ 9 ]. Although a lot of effort and hope has been put on vaccines, as a strategy to protect this group of patients, the large randomized clinical trials excluded immunocompromised patients in their design.…”
Section: Discussionmentioning
confidence: 99%
“…Although the severity of the COVID-19 illness caused by the Omicron variant appears to have been reduced compared to that in the pre-Omicron era, probably owing to the attenuated virulence of the strain and the pre-existing immunity derived from previous infection and vaccination, its rapid spread has resulted in a cumulative increase in acute care visits, hospitalizations, and mortality events [ 6 , 7 ]. Additionally, there are still concerns regarding the impact of COVID-19 on vulnerable populations, such as immunocompromised patients and those with multimorbidity, who have increased risks of hospitalization and prolonged illness durations, even in the Omicron era [ 8 , 9 , 10 , 11 ]. As one of the populations susceptible to this contagious disease, hemodialysis (HD) patients have a remarkably high risk of COVID-19 infection and disease progression owing to the need for regular dialysis visits, multiple comorbidities, and impaired immune responses to pathogens and vaccinations [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%